2021
DOI: 10.1186/s40537-021-00518-7
|View full text |Cite
|
Sign up to set email alerts
|

Normalization and outlier removal in class center-based firefly algorithm for missing value imputation

Abstract: A missing value is one of the factors that often cause incomplete data in almost all studies, even those that are well-designed and controlled. It can also decrease a study’s statistical power or result in inaccurate estimations and conclusions. Hence, data normalization and missing value handling are considered the major problems in the data pre-processing stage, while classification algorithms are adopted to handle numerical features. In cases where the observed data contained outliers, the missing value est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…It also showed that C3FA + Dist had better results at a low missing data < 20%. The C3FA method had a good performance on the missing data of 40% through the MCAR mechanism which is in line with previous research [28,29]. Other experimental results showed that the C3FA-STD method produced the best performance evaluation when the dataset had a reasonably high amount of missing data (60%).…”
Section: Analysis and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It also showed that C3FA + Dist had better results at a low missing data < 20%. The C3FA method had a good performance on the missing data of 40% through the MCAR mechanism which is in line with previous research [28,29]. Other experimental results showed that the C3FA-STD method produced the best performance evaluation when the dataset had a reasonably high amount of missing data (60%).…”
Section: Analysis and Discussionsupporting
confidence: 88%
“…Further research conducted by the author where at the beginning the imputation method, the author employed a standardization and outlier identification strategy. The result showed combining normalization and outlier removals in C3FA was an efficient technique for obtaining actual data in handling missing values [29]. However, the imputation method with the class center-based firefly algorithm was not analyzed on the categorical datasets in other previous studies.…”
Section: Fig 1 the Pattern Of Missing Valuesmentioning
confidence: 96%
“…A reliable indicator of a set of data's degree of dispersion is the median absolute deviation (MAD). MAD is a more widely used outlier removal technique and a known statistical methodology that uses the standard deviation from the mean, which was recommended by different researchers [ [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ]. The ionosonde measures the electron densities for each layer as well as their estimated altitudes as functions of time [ 33 , 34 ].…”
Section: Methodology and Datamentioning
confidence: 99%
“…The EAS was normalized to be able to predict the target value of Predictive Entrepreneurship Opportunity (PEO). This data was pre-processed to suit ML algorithms, involving missing value imputation, outlier removal, and normalization of numerical values (Nugroho et al, 2021). Key features encapsulating the SECURE pillars were selected for their potential impact on ML model performance.…”
Section: Development Of Machine Learning Modelmentioning
confidence: 99%